2017
DOI: 10.18632/oncotarget.16043
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of simultaneous 18F-FDG-PET/MRI predict tumor stage and several histopathological features in uterine cervical cancer

Abstract: The purpose of this study was to analyze associations between apparent diffusion coefficient (ADC) and standardized uptake values (SUV) values and different histopathological parameters in uterine cervical cancer. 21 patients with primary uterine cervical cancer were involved into the study. All patients underwent a whole body simultaneous18F-FDG PET/MRI. Mean and maximum SUV were noted (SUVmean and SUVmax). In all tumors minimal, mean, and maximal ADC values (ADCmin, ADCmean, and ADCmax) were estimated. Combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 28 publications
3
39
0
Order By: Relevance
“…Currently, most functional MRI clinical applications as part of hybrid PET/MRI apply DWI, which informs about the water diffusivity in tissues and providing valuable information on tissue cellularity and membrane integrity. Most reports correlating SUV with apparent diffusion coefficient (ADC) are based on fused or hybrid PET/MRI data, focusing on cervical cancer ( 13 , 14 , 16 , 18 , 20 , 21 , 29 , 36 ), and only one study each is about endometrial cancer and uterine cancer each ( 15 , 17 ).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, most functional MRI clinical applications as part of hybrid PET/MRI apply DWI, which informs about the water diffusivity in tissues and providing valuable information on tissue cellularity and membrane integrity. Most reports correlating SUV with apparent diffusion coefficient (ADC) are based on fused or hybrid PET/MRI data, focusing on cervical cancer ( 13 , 14 , 16 , 18 , 20 , 21 , 29 , 36 ), and only one study each is about endometrial cancer and uterine cancer each ( 15 , 17 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…In a study focusing on uterine cancer, Surov et al found that the combination of SUV and ADC provided the greatest correlation with the proliferation biomarker Ki-67 ( 15 ). Ki-67 correlated significantly with SUVmax ( r = 0.59, p = 0.005) and ADCmin (0.48, p = 0.03).…”
Section: Review Of Literaturementioning
confidence: 99%
“…There were studies, which showed that ADC min had stronger correlations with KI 67, and can better reflect proliferation potential of malignant lesions [ 7 , 8 ]. However, the reported data were based on small number of investigated tumors/patients.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we re-analyzed our previous data regarding associations between ADC parameters and histopathological findings [9] , [10] , [11] , [12] , [13] , [14] . Overall, 134 patients with different tumors were acquired for the analysis ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%